Antibody levels anti-Babesia bigemina and Babesia bovis in calves of Nelore and Ibagé breeds and Nelore crosses - Madruga, Claudio Roberto; Aycardi, Eduardo; Kessler, Raul Henrique; Schenk, Maria Aparecida Moreira; Figueiredo, Geraldo Ramos de; Curvo, João Baptista Esmela (Pesquisa Agropecuaria Brasileira, 2014)
Antibody levels of Babesia bigemina and Babesia bovis were analysed by the indirect fluorescent antibody technique in calves of Nelore and Ibagé breeds, Nelore x Fleckvieh and Nelore x Chianina, and Nelore x Charolais cross up to weaning age. Three and 14 day-old calves of some breeds and crosses showed significant positive correlation with the immunoglobulins anti - B. bigemina and/or B. bovis of the cows. Lower levels of immunoglobulins against B. bigemina were found between 28 and 56 days of age and against B. bovis between 56 and 84 days of age. The active antibody production was observed against B. bigemina at 84 days and at 112 days of age against B. bovis. The antibody level anti B. bigemina was generally higher than anti -B. bovis and the antibody curve was more similar to Nelore breed and its calf crosses than to the lbagé breed. Although the region is considered to be enzootically stable, it was concluded that there is a critical time of low humoral resistance during which the clinical symptoms of babesiosis can occur.